2020
DOI: 10.3390/md18060303
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oxygenated Constituents from a Marine Alga-Derived Fungus Aspergillus giganteus NTU967

Abstract: Agar-based disc diffusion antimicrobial assay has shown that the ethyl acetate extract of the fermented broth of Aspergillus giganteus NTU967 isolated from Ulva lactuca exhibited significant antimicrobial activity in our preliminary screening of bioactive fungal strains. Therefore, column chromatography of the active principles from liquid- and solid–state fermented products of the fungal strain was carried out, and which had led to isolation of eleven compounds. Their structures were determined by spectral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…They also reported that the compounds Nortryptoquivaline, 2,4-dihydroxy-3-methylacetophenone, chevalone C from Neosartorya siamensis exhibited strong effects against DNA and intracellular accumulation in lung cancer cells as well as induced cytotoxicity against the cancer cells and the cell death in lung cancer. The 3-hydroxy, benzenemethanol, 2-bromogentisyl alcohol, 2-chlorogentisyl alcohol, and Epoxydon 6-dehydroxy-6-bromogabosine C compounds purified from the secondary metabolic of P. concentricum exhibited anti-cancer activity against the human caucasian colon adenocarcinoma cells line [18]. The pentacyclic decalinoylspirotetramic acid and pyrenosetin D from Pyrenochaetopsis sp.…”
Section: Systematic Literature Review Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…They also reported that the compounds Nortryptoquivaline, 2,4-dihydroxy-3-methylacetophenone, chevalone C from Neosartorya siamensis exhibited strong effects against DNA and intracellular accumulation in lung cancer cells as well as induced cytotoxicity against the cancer cells and the cell death in lung cancer. The 3-hydroxy, benzenemethanol, 2-bromogentisyl alcohol, 2-chlorogentisyl alcohol, and Epoxydon 6-dehydroxy-6-bromogabosine C compounds purified from the secondary metabolic of P. concentricum exhibited anti-cancer activity against the human caucasian colon adenocarcinoma cells line [18]. The pentacyclic decalinoylspirotetramic acid and pyrenosetin D from Pyrenochaetopsis sp.…”
Section: Systematic Literature Review Methodologymentioning
confidence: 99%
“…The marine environment which includes the water, sediments, invertebrates, driftwood as well as marine mammals represents a rich source of fungi [18]. Up-to-date studies have estimated there are more than 10,000 marine fungal species, including the fungi belong to the Ascomycota and Basidiomycota phyla [22].…”
Section: Potential Of Secondary Metabolic Substances From Marine Fungi As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the ADMET results, quinadoline B indicated high gastrointestinal (GI) absorption, low blood-brain barrier penetrability, and high drug-likeness ( Quimque et al, 2020 ). Quinadoline B has also been extracted from Aspergillus giganteus Wehmer, 1901 NTU967 which was isolated from the marine alga, Ulva lactuca ( Chen JJ. et al, 2020 ), and Aspergillus sp.…”
Section: Natural Products Against Sars-cov-2: Computational To Preclinical Studiesmentioning
confidence: 99%
“…Tabel 1. [22][23][24] Tabel 1 Aktivitas sitotoksik dari metabolit jamur yang berasosiasi dengan spons laut [22][23][24][25][26][27] No Metabolit yang diisolasi…”
unclassified